Descriptive Analysis of the E-Textbook Situation in Quebec - Roy, Normand; Boyer, Priscilla; Lebrun, Monique; Samson, Ghislain (Formation et profession)

(untitled) (Centre de recherche interuniversitaire sur la formation et la profession enseignante (CRIFPE), 2022)
In this study, we will describe and compare the digital components present in Quebec’s e-textbooks for five different subject matters between 2015 and 2018. To do so, we analyzed 133 e-textbooks from secondary 1 to 5 using different observation grids. The added value of technology in e-textbooks was assessed based on three categories: hypertextualization (intertextuality, hypertextuality and hypertext), multimodality (videos, images and animations) and interaction (feedback, activities and simulation). Results showed that half of the e-textbooks are only digitized versions of the paper textbooks. The other half introduce different varieties of multimedia. To conclude, we will propose a reflection on the value of e-textbooks in the high school system.